MALE GAZE DALAM FILM THE HANDMAIDEN - Mubarok, Ilham; Pudjo Santoso, Hedi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
South Korean film industry (Hallyuwood) is one of the most promising film industry in the world along with Hollywood and Bollywood. This film industry is producing varieties of genre, one of them is queer film. Queer film is a film which tells stories about people from sexual minorities such as lesbian, gay, bisexual, and transgender. Ideally, queer film uses homonormativity as the main ideology in order to convey the stories from sexual minorities well. But, one of South Korean queer film, The Handmaiden, which tells story about lesbian women called attention because some critics and viewers accused it for portraying lesbian women in male gaze. Male gaze would disrupt the discourse of body, sexuality, and character development of lesbian women which is should be portrayed in homonormativity. The aim of this research is to describe the discourse of body, sexuality, and character development of lesbian women in film The Handmaiden. The subject of this research is 22 scenes from the film which are related to body, sexuality, and character development of lesbian women. This research used critical paradigm and Sara Mills’ Discourse Analysis method which consists of: character analysis, fragmentation analysis, focalization analysis, and schemata analysis. The research used two main theories: Laura Mulvey’s male gaze theory and queer theory to describe the discourse of body, sexuality, and character development of lesbian women in the film. The result of the research showed that male gaze was found in the film but not as dominant ideology. Instead, the film used homonormativity as the dominant ideology to describe the body, sexuality, and character development of lesbian women.